2021
DOI: 10.1021/acs.jproteome.1c00882
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Serology by Mass Spectrometry: Readout of the SARS-CoV-2 Antibody Repertoire

Abstract: Methods of antibody detection are used to assess exposure or immunity to a pathogen. Here, we present Ig-MS, a novel serological readout that captures the immunoglobulin (Ig) repertoire at molecular resolution, including entire variable regions in Ig light and heavy chains. Ig-MS uses recent advances in protein mass spectrometry (MS) for multiparametric readout of antibodies, with new metrics like Ion Titer (IT) and Degree of Clonality (DoC) capturing the heterogeneity and relative abundance of individual clon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 50 publications
(119 reference statements)
2
27
0
Order By: Relevance
“…An alternative MS-based method potentially useful for the assessment of IgG Fc glycosylation in COVID-19 is middle-up antibody analysis, as presented for anti-RBD IgG in a study by Melani et al Even though this method is promising, the observed high complexity due to multiple different amino acid sequences and glycan structural heterogeneity complicates Fc glycosylation analysis using this approach [ 34 ].…”
Section: Methods For the Assessment Of Antibody Glycosylation In Covid-19mentioning
confidence: 99%
“…An alternative MS-based method potentially useful for the assessment of IgG Fc glycosylation in COVID-19 is middle-up antibody analysis, as presented for anti-RBD IgG in a study by Melani et al Even though this method is promising, the observed high complexity due to multiple different amino acid sequences and glycan structural heterogeneity complicates Fc glycosylation analysis using this approach [ 34 ].…”
Section: Methods For the Assessment Of Antibody Glycosylation In Covid-19mentioning
confidence: 99%
“…Although attempts were made to de novo sequence these antibodies at the intact protein level, the results were limited to a few sequence tags. During the SARS-CoV-2 pandemic, Melani et al 105 focused their profiling efforts on the vaccine-targeted Spike protein receptor-binding domain. The approach is named Ig-MS and features two novel metrics for capturing the intensity and complexity of the antibody response.…”
Section: Protein-centric Sequencing Of Endogenous Antibodiesmentioning
confidence: 99%
“…In addition, plasma from 6 vaccinated individuals (3 boosted and 3 not boosted) was collected following infection with Omicron SARS-CoV-2 between December 29, 2021, and January 16, 2022 (Table S1). Plasma preparation was conducted as previously reported . As a standard positive control, we used a commercially obtained plasma sample (CS1) from a convalescent patient infected at the beginning of the pandemic (AllCells).…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The analysis was performed as previously described . Briefly, samples were delivered to the mass spectrometer at a flow rate of 1 μL/min in a fully automated fashion using a a PAL3 robot (CTC Analytics) coupled with a SampleStream flowcell (Integrated Protein Technologies).…”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation